Analysis of Trends in Researches on STEAM (STEM + Art) Made in Turkey - Gülhan, Filiz (Fırat University, 2022)
STEM (Science-Technology-Engineering-Mathematics) in the education field, is frequently applied and researched all over the world. Thereafter the STEAM (STEM + Art) approach, which advocates that art contribution will bring full integration in a transdisciplinary manner, is also spreading rapidly. The research aims to examination of published research on studied STEAM education in Turkey since 2017 and to determine whether it shows similar trends with STEM researches. In this survey study, 36 studies were reached with PRISMA flow chart and the studies were subjected to descriptive analysis in terms of various features. As a result of the research, it was concluded that the qualitative research method was used the most, worked with middle school students, and the interview and survey was used for data collection. In addition, it has been concluded that applied STEAM researches are mostly done within the scope of Science lesson, often take around 5 weeks, and the most researched variables are attitudes and skills. In STEAM studies that do not include coursework, it has been determined that the most studied area is attitudes towards STEAM education. Since STEAM is proceeding with trends similar to STEM, it made suggestions for researchers.

STEM (Science-Technology-Engineering-Math) [Türkçesiyle (Fen-Teknoloji-Mühendislik-Matematik)] eğitiminin sıklıkla uygulanması ve araştırılmasını takiben; STEM’e “Art (sanat)” katkısının transdisipliner biçimde tam bir entegrasyonu oluşturacağını savunan STEAM [STEM + A (Sanat)] yaklaşımı da önemli bir araştırma alanı olmuştur. Bu araştırmada Türkiye’de 2017 yılından beri çalışılan STEAM eğitimi konusunda yayımlanmış araştırmaların incelenmesi ve STEM araştırmalarına benzer eğilimler gösterip göstermediğinin tespit edilmesi amaçlanmıştır. Bu amaçla yapılan tarama çalışmasında 36 araştırmaya ulaşılmış, PRISMA akış şeması izlenerek araştırmalar çeşitli özellikleri bakımından betimsel analize tabi tutulmuştur. Araştırma sonucunda STEAM ile ilgili alan yazında en çok nitel araştırma yönteminin kullanıldığı, ortaokul öğrencileriyle çalışıldığı, veri toplamada en çok görüşme ve test/anket kullanıldığı sonucuna varılmıştır. Ayrıca deneysel ders uygulaması içeren araştırmaların en çok Fen Bilimleri dersi kapsamında yapıldığı, araştırmaların STEAM uygulamalarının sıklıkla 5 hafta civarında sürdüğü, en çok araştırılan değişkenlerin tutum ve beceriler olduğu sonucuna ulaşılmıştır. Deneysel ders uygulaması içermeyen STEAM araştırmalarında ise en çok incelenen alanın STEAM eğitimine yönelik tutumlar olduğu tespit edilmiştir. STEAM’in STEM’e benzer biçimde eğilimlerle ilerlediğinden hareketle araştırmacılara yönelik önerilerde bulunmuştur.
Türkiye’de Yapılmış STEAM / [STEM + A (Sanat)] Araştırmalarındaki Eğilimlerin Analizi
Keywords: Other Fields of Education; Alan Eğitimleri